Genetic Effects Of Combining Ability On Forage Quality Traits And Forage Yield In Diallel Crosses Of Oats (Avena Sativa L.) (Applied Biological Research, 2014)
Studies in oats (Avena sativa L.) were carried out to generate  information on combining ability (general and specific), nature and  magnitude of gene effects and heterosis for forage quality and yield. The  experimental material comprised of 10 diverse parents and 45 F1 crosses  (excluding reciprocals) generated through a 10 x 10 diallel mating  design. Significant interaction between combining ability effects were  observed for all the quality traits and yield. The estimates of additive  variance were higher in magnitude than their corresponding dominance  variance estimates indicating the role of additive gene action, except  green forage yield and dry matter yield. The parent SKO-213 had highly  significant and desirable GCA effects for crude protein content, SKO 210 for neutral detergent fibre, SKO-204 for acid detergent fibre, SKO 208 for crude fibre parent, SKO-207 for ash content and SKO-212 for  both green forage and dry matter yields. Crosscombinations viz., SKO 212 x SKO-213, SKO-204 x SKO-211, SKO-205 x Sabzaar, Sabzaar x SKO-212 and SKO-205 x SKO-211 exhibited high and desirable sca and  heterobeltiosis effects simultaneously for all the quality traits, green  forage yield and dry matter yield ha-1.
Keywords: Avena sativa; combining ability; forage quality; GCA; heterobeltiosis; SCA; yield